2020
DOI: 10.1038/s41598-020-70107-w
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a patient-specific system for mandible-first bimaxillary surgery: ramus and implant positioning precision assessment and guide design comparison

Abstract: In orthognathic surgery, the use of patient-specific osteosynthesis devices is a novel approach used to transfer the virtual surgical plan to the patient. The aim of this study is to analyse the quality of mandibular anatomy reproduction using a mandible-first mandibular-PSI guided procedure on 22 patients. Three different positioning guide designs were compared in terms of osteosynthesis plate positioning and mandibular anatomical outcome. PSIs and positioning guides were designed according to virtual surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…The present protocol was approved by the Sant'Orsola-Malpighi University Hospital ethics committee (approval number 238/2012/0/Disp PL02, amended 18/10/2016); the study conformed to the principles of the Declaration of Helsinki. Written informed consent was obtained from all the patients upon enrollment in the trial 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present protocol was approved by the Sant'Orsola-Malpighi University Hospital ethics committee (approval number 238/2012/0/Disp PL02, amended 18/10/2016); the study conformed to the principles of the Declaration of Helsinki. Written informed consent was obtained from all the patients upon enrollment in the trial 2 .…”
Section: Methodsmentioning
confidence: 99%
“…1B). Three guide types were used throughout the trial and were compared in our previous work on this cohort of patients 2 . The custom 3D-printed titanium alloy (Ti6Al4V) plates were designed to fixate the proximal and distal mandibular fragments in their planned positions using the screw fixation holes, drilled according to the positioning guides, as reference.…”
Section: Case Planning and Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…In the pursuit of a technique which could reliably reproduce the digitally planned spatial relationship between the mandibular condyle-bearing segments and teeth-bearing segment, we combined the mandible-first approach with a PSI-guided mandibular procedure and demonstrated that it leads to a satisfactory reproduction of the planned mandibular anatomy [2].…”
Section: Introductionmentioning
confidence: 99%